2014
DOI: 10.1111/ecc.12187
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatraemia in cancer: association with type of cancer and mortality

Abstract: Hyponatraemia is common in patients with cancer. The objectives of this study are to investigate the severity distribution of hyponatraemia and its association with mortality. We retrospectively reviewed medical records for patients admitted to a national centre for cancer care and research in Qatar between 2008 and 2012. A model was built through multivariate analyses to investigate the role of hyponatraemia in mortality. Patients were grouped into those who had moderate-severe hyponatraemia (Na < 130) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 34 publications
6
35
0
1
Order By: Relevance
“…Furthermore, it was found an independent inverse relationship between sNa levels and mortality in patients with chronic diseases, also in case of mild hyponatremia . Similar findings were reported in many studies in the oncology setting . It was even hypothesized that cancer‐related hyponatremia may adversely affect the response to anticancer‐targeted treatment, suggesting the potential benefit resulting from an early detection and proper treatment of the disorder.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, it was found an independent inverse relationship between sNa levels and mortality in patients with chronic diseases, also in case of mild hyponatremia . Similar findings were reported in many studies in the oncology setting . It was even hypothesized that cancer‐related hyponatremia may adversely affect the response to anticancer‐targeted treatment, suggesting the potential benefit resulting from an early detection and proper treatment of the disorder.…”
Section: Introductionsupporting
confidence: 76%
“…12 Similar findings were reported in many studies in the oncology setting. 1,6,13 It was even hypothesized that cancer-related hyponatremia may adversely affect the response to anticancer-targeted treatment, 14 suggesting the potential benefit resulting from an early detection and proper treatment of the disorder. The degree and the duration of hyponatremia, along with the presence and severity of symptoms, have to be simultaneously considered in order to select the optimal treatment for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that hyponatremia (<135 mEq/L) was present in 47% of newly admitted cancer patients, 2) and 3.7-33.8% of cancer patients had serum sodium concentrations below 130 mEq/L. 3,4) In particular, prostate, pancreatic, and small cell lung cancers were frequently associated with the onset of hyponatremia. 4) Administration of cisplatin (CDDP), a platinum anticancer agent, has been related to the development of hyponatremia, although renal failure, nausea, vomiting, and ototoxicity were the major adverse events.…”
Section: Introductionmentioning
confidence: 98%
“…This late diagnosis and treatment pattern may therefore be related to inadequate awareness about cancer prevention and screening programs available in Saudi communities [28]. Currently, there are more than 15 oncology care settings in the KSA offering a variety of services including: intensive cancer care management units, consultation services, routine screening, cancer therapy, rehabilitation, home healthcare programs, outpatient clinics, and supportive care services (diet center, physical therapy, patient education, pharmacy, and both institutional units for palliative care with translation and religious authorities to attend the spiritual needs of the terminally ill cancer patients) as well as home-based care [19,29]. The first palliative care program began more than 20 years ago at King Faisal Specialist Hospital and Research Center, Riyadh and programs are now available in a number of hospitals serving more than 5,000 patients annually [30].…”
Section: Cancer Care In the Kingdom Of Saudi Arabiamentioning
confidence: 99%